2010
DOI: 10.3997/1873-0604.2010070
|View full text |Cite
|
Sign up to set email alerts
|

Combining multiple signals of an electromagnetic induction sensor to prospect land for metal objects

Abstract: Buried unexploded ammunition is a major problem on arable land in former battle areas. Many battlefields of the First World War (WWI) still contain a lot of unexploded shells just below the plough layer, posing serious threats to soil editors and trenchers. Electromagnetic induction (EMI) sensors have been used for a variety of agricultural and archaeological purposes to map the natural soil variability and to locate buried archaeological remains. Besides its sensitivity to variations in soil texture and anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…As shown also in Saey et al . () and Martinelli & Osella (), the sensitivity of EMI to strong conductors guarantees the detection of such subsurface structures, but it can lead to spatially exaggerated anomalies in the EMI maps. In the 1PRP EC a map the width of the linear anomaly is 3 m or more, which hampers estimation of the true dimensions of the detected structure.…”
Section: Resultsmentioning
confidence: 99%
“…As shown also in Saey et al . () and Martinelli & Osella (), the sensitivity of EMI to strong conductors guarantees the detection of such subsurface structures, but it can lead to spatially exaggerated anomalies in the EMI maps. In the 1PRP EC a map the width of the linear anomaly is 3 m or more, which hampers estimation of the true dimensions of the detected structure.…”
Section: Resultsmentioning
confidence: 99%
“…In our experience, the extreme negative and positive values can be mostly attributed to buried metallic objects, although it should be noted that small or large anomalies compared with the background values could be caused by the 3D‐sensitivity of the electromagnetic method (Callegary et al , ). Following Saey et al (), a data fusing methodology was applied to combine the four simultaneous σ a measurements into one indicator. As a result, both point anomalies, which can be attributed to the presence of separated buried metallic objects, and a linear pattern running northeast‐southwest, representing a metal tube dug within the soil, could be retrieved (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Buried massive metallic objects, possibly unexploded ordnance buried within the soil up to 1.0 m depth, can be identified by comparing local spatial data outliers within the σ a and κ a data. These metallic features show a clearly identifiable signature in the σ a data, as explained by Saey et al (2011), because they show a characteristic deviation from the background value for the different coil configurations. The sensitivity of the different coil configurations to buried metal varies considerably and the metal objects show a different signature according to their depth of occurrence.…”
Section: Metal Delineationmentioning
confidence: 93%
“…From Saey et al (2011) could be concluded that massive metal objects within the topsoil (0-0.4 m) sign as very negative anomalies within the 1HCP configuration. Therefore, this coil configuration is considered as very sensitive for metal objects within the topsoil.…”
Section: Metal Delineationmentioning
confidence: 98%
See 1 more Smart Citation